Teachers' and Students' Needs for Mathematical Literacy-Based Comics - Audiyah Shinta Bella; Tri Candra Wulandari; Isbadar Nursit; Budi Hartono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to analyze the need for developing mathematical comics as a visual learning medium to improve fifth-grade students' mathematical literacy skills on fraction operations. The study used a Research and Development (R&D) approach with a (4-D) model, focused on the define stage. The research subjects consisted of 8 homeroom teachers and 1 principal, as well as 29 students at Rajawali Elementary School, Tanah Bumbu Regency. Data were collected through questionnaires and interviews, then analyzed descriptively quantitatively and qualitatively. The results of the analysis indicate that learning is still dominated by textbooks, so students have difficulty understanding and interpreting story problems. Teachers and students showed high support for print-based visual media that can be accessed offline. All students expressed a need and interest in mathematical comics to improve mathematical literacy. These findings emphasize the urgency of developing contextual and adaptive print-based mathematical comics to strengthen elementary school students' mathematical literacy skills.